Home visits as a strategy for health promotion by nursing - Jucelia Salgueiro Nascimento; Laís de Miranda Crispim Costa; Regina Maria dos Santos; Danielly Santos dos Anjos (Universidade de Fortaleza, 2014)
Objective: To analyze the domiciliary visit performed by nurses in the Family Health Strategy as an activity to promote health. Methods: Exploratory/descriptive study with qualitative approach. The subjects were nine nurses of the Primary Health Units from Health Districts in Maceió-AL. Data was collected through semi-structured interviews in the months from April to August 2012 and were analyzed using content analysis and in light of the theoretical framework of Health Promotion. Results: The nurses recognize that the domiciliary visit can be a way to promote the health of individuals, families and community, but, in daily life, action maintains focus on disease, with curative actions of individual character, which do not take into account the social context where the user and his family are inserted. Conclusion: It is considered that the use of home visits by nurses in the family health strategy as a health promotion activity is still incipient because, although the nurses recognize the need for change in the model of care, in practice, it is observed that the focus of this action is directed to the biological model. doi:http://dx.doi.org/10.5020/18061230.2013.p513